FROM REPUBLICAN SCHOLAR TO FEDERALIST JUDGE: THE TRANSFORMATION OF JOSEPH STORY - Spare, Bethany (Kansas State University. Dept. of History, 2012)
Joseph Story sat on the Supreme Court with Chief Justice John Marshall and in many ways it seemed like Marshall simply overshadowed the younger justice. However, Story began his political and legal career as a member of the Republican Party. What changed his mind, why did he change from a supporter of the Jeffersonian Democratic-Republicans to a firm defender of the Federalist Party while on the Supreme Court? Story‟s letters, speeches, and Commentaries were analyzed to find evidence. Kent Newmyer, Gerald Dunne, and Joseph McClellan are three modern historians who were consulted as well. Story was not a man to be led by others‟ opinions, once he was convinced in his own mind that a course of action was right, he would not be swayed until he saw that that course was no longer allowing him to follow his conscience. While a young man he defended the Republican Party but as he grew to respect the law and especially the English common law—practiced also in America—the Republican Party became more and more restrictive. Finally convinced that the best way was to defend the “science of law,” and the study of jurisprudence over all other considerations, he saw that the Federalist Party would allow him to do just that. An examination of his decisions in Prigg v. Pennsylvania and the Amistad cases, demonstrate how Story would defend the Constitution and the law over all other secondary considerations, even against his personal beliefs. Rather than being overshadowed by Marshall‟s personality, Story decided on a course of action first and then saw that the Federalist party, rather than the Republican would allow him to follow that course.
Keywords: Supreme Court; Federalist Party; Republican Party; Joseph Story